Vitamina B12 (Cianocobalamina) e oxidação da glicose pela Escherichia coli - Villela, Gilberto G. (Acta Biológica Paranaense, 1976)
Vitamina B12 (Cianocobalamina) e oxidação da glicose pela Escherichia coli